2009
DOI: 10.1097/scs.0b013e31819b9671
|View full text |Cite
|
Sign up to set email alerts
|

Computational Fluid Dynamic Study on Obstructive Sleep Apnea Syndrome Treated With Maxillomandibular Advancement

Abstract: Maxillomandibular advancement is one of the treatments available for obstructive sleep apnea. The influence of this surgery on the upper airway and its mechanism are not fully understood. The present research simulates the flow fields of narrowed upper airways of 2 patients with obstructive sleep apnea treated with maxillomandibular advancement. The geometry of the upper airway was reconstructed from computed tomographic images taken before and after surgery. The consequent three-dimensional surface model was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(34 citation statements)
references
References 18 publications
4
30
0
Order By: Relevance
“…The same group has also studied airway resistance in asthmatics (23), finding that changes in forced expired volume in one second (FEV 1 ) following inhalation of a bronchodilator correlated well with total and distal airway resistance, as calculated using CFD for each of the subjects. In a similar clinically relevant application, Yu et al (113) used CFD to assess the influence of maxillomandibular advancement (a treatment of obstructive sleep apnea) on airway resistance. Computed tomographic (CT) measurement showed that postsurgery the narrowest region of the airway had increased in cross-sectional area.…”
Section: Airway Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…The same group has also studied airway resistance in asthmatics (23), finding that changes in forced expired volume in one second (FEV 1 ) following inhalation of a bronchodilator correlated well with total and distal airway resistance, as calculated using CFD for each of the subjects. In a similar clinically relevant application, Yu et al (113) used CFD to assess the influence of maxillomandibular advancement (a treatment of obstructive sleep apnea) on airway resistance. Computed tomographic (CT) measurement showed that postsurgery the narrowest region of the airway had increased in cross-sectional area.…”
Section: Airway Resistancementioning
confidence: 99%
“…The complexity of the human tracheobronchial tree has restricted the majority of previous CFD studies to small regions of the airway tree, with the complex domain represented by idealized cylindrical geometries with simple bifurcations over one to several generations [e.g., (19-21, 66, 115, 116)], or anatomically consistent (but with smoothed circular cross sections) geometry (98). The physical domain has previously been represented on the basis of the classic symmetric Weibel model A (102) or the asymmetric Horsfield model (43); however, it is now possible to compute airflow in physical domains that are anatomically accurate and subject specific [e.g., (3,9,24,25,56,61,113)]. The advantage of this approach is that the influence of anatomical features such as curved airways, cartilage ridges, and diameter variation along an airway can be incorporated correctly.…”
Section: The Interaction Between Geometry and Airflowmentioning
confidence: 99%
“…Computational fluid dynamics (CFD) techniques can be used to simulate airflow through three-dimensional (3D) reconstructions of the nasal cavity, providing highly detailed assessments of airflow patterns, pressure, and, in particular, bilateral and unilateral NR. A number of studies have been conducted using 3D nasal CFD models, some of which have focused specifically on the effects that common pathologies and surgical changes have on nasal airflow, [12][13][14][15][16][17][18][19][20][21][22][23][24][25] indicating a growing maturity in the use of CFD methods.…”
Section: N Asal Airway Obstruction (Nao) Is a Common Health Conditionmentioning
confidence: 99%
“…2) [42]. Future use of these imaging techniques with CFD calculations, in the selection of patients for OSAHS surgery, has already been suggested [47,48].…”
Section: Oral Appliance Therapymentioning
confidence: 99%
“…Oral appliance therapy may be a first-line treatment in snorers with or without excessive daytime sleepiness [42,[47][48]. The 2005 update of the practice parameters published by the American Academy of Sleep Medicine [11], recommends oral appliance therapy for patients with mild-to-moderate OSAHS who prefer this treatment to CPAP.…”
Section: Oral Appliance Therapymentioning
confidence: 99%